Introducing a new 7-ring fused diindenone-dithieno[3,2-b:2',3'-d]thiophene unit as a promising component for organic semiconductor materials - Fell, Valentin H. K.; Cameron, Joseph; Kanibolotsky, Alexander L.; Hussien, Eman J.; Skabara, Peter J. (Beilstein Journal of Organic Chemistry, 2022)
A novel π-conjugated molecule, EtH-T-DI-DTT is reported, which is fused, rigid, and planar, featuring the electron-rich dithieno[3,2-b:2’,3’-d]thiophene (DTT) unit in the core of the structure. Adjacent to the electron-donating DTT core, there are indenone units with electron-withdrawing keto groups. To enable solubility in common organic solvents, the fused system is flanked by ethylhexylthiophene groups. The material is a dark, amorphous solid with an onset of absorption at 638 nm in CH2Cl2 solution, which corresponds to an optical gap of 1.94 eV. In films, the absorption onset wavelength is at 701 nm, which corresponds to 1.77 eV. An ionisation energy of 5.5 eV and an electron affinity of 3.3 eV were estimated by cyclic voltammetry measurements. We have applied this new molecule in organic field effect transistors. The material exhibited a p-type mobility up to 1.33 × 10−4 cm2 V−1 s−1.
Keywords: dithienothiophene (DTT); fused ring system; organic field-effect transistor (OFET); organic semiconductor; thienoacene